2007
DOI: 10.1021/bi700336y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Binding Sites of the Haloalkane Dehalogenase DhlA from Xanthobacter autotrophicus GJ10

Abstract: The catalytic site of haloalkane dehalogenase DhlA is buried more than 10 A from the protein surface. While potential access channels to this site have been reported, the precise mechanism of substrate import and product export is still unconfirmed. We used computational methods to examine surface pockets and their putative roles in ligand access to and from the catalytic site. Computational solvent mapping moves small organic molecule as probes over the protein surface in order to identify energetically favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Many globular enzymes possess active sites buried in the protein core, and there is growing evidence that the access of substrates to the active site or release of products can be a determinant of their catalytic activity [1][2][3][4][5][6][7][8][9][10][11][12][13] and substrate specificity. [1][2][3][5][6][7][8]10,[13][14][15][16][17][18][19][20][21] Mechanisms of ligand exchange between buried active sites and bulk solvent and the effects of mutations on the exchange process are often less well understood than the mechanisms of chemical reactions taking place in the active sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many globular enzymes possess active sites buried in the protein core, and there is growing evidence that the access of substrates to the active site or release of products can be a determinant of their catalytic activity [1][2][3][4][5][6][7][8][9][10][11][12][13] and substrate specificity. [1][2][3][5][6][7][8]10,[13][14][15][16][17][18][19][20][21] Mechanisms of ligand exchange between buried active sites and bulk solvent and the effects of mutations on the exchange process are often less well understood than the mechanisms of chemical reactions taking place in the active sites.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][5][6][7][8]10,[13][14][15][16][17][18][19][20][21] Mechanisms of ligand exchange between buried active sites and bulk solvent and the effects of mutations on the exchange process are often less well understood than the mechanisms of chemical reactions taking place in the active sites.…”
Section: Introductionmentioning
confidence: 99%
“…acting on halogenated aliphatic hydrocarbons catalyze carbon-halogen bond cleavage, leading to an alcohol, a halide ion, and a proton as the reaction products (7). Haloalkane dehalogenases originating from various bacterial strains have potential for application in bioremediation technologies (4,6,22), construction of biosensors (2), decontamination of warfare agents (17), and synthesis of optically pure compounds (19). Recent evolutionary study of haloalkane dehalogenase sequences revealed the existence of three subfamilies, denoted HLD-I, HLD-II, and HLD-III (3).…”
mentioning
confidence: 99%
“…It is assumed that S 2 and S 3 play important roles in the exchange of modulators between the active site and the reaction medium when the direct channel to the active site is not easily accessible [49]. In fact, when tropolone is in MTPa, MTPb and MTPc at the end of the channels S 2 and S 3 , respectively, are the sites that show higher affinity for binding [50]. Possible energetically favorable channels in 2Y9X; A) the identified channels in snapshot 4 of 10ns MD simulation are depicted as color spheres: channel S 1 (green), S 2 (blue) and S 3 (purple).…”
Section: Analysis Of Channelsmentioning
confidence: 99%